PENGGUNAAN BETON STYROFOAM RINGAN DENGAN TULANGAN DARI TALI TAMBANG PLASTIK UNTUK PANEL PLAT ATAP - Bastoni Hassasi (Politeknik Negeri Sriwijaya, 2013)
The utilization of lightweight material will decrease the structural weight that in turn will benefit to the overall structures. Styrofoam with specific gravity range from 13 to15 kg/m3 is appropriate to be used as aggregate for lightweight concrete among other as the material for roof slab. Prior to utilization research is required in order to understood the feasibility of the material for applicationThe aimed of this research is to study the characteristic of lightweight styrofoam concrete with string of plastic inside the panel as a roof material. In this study, there are 6 pieces as testing material with 1500 mm long, 500 mm wide and 70 mm thick at various reinforcement; without string of plastic, with reinforced diameter10 mm and14 mm. The slab panel is made up from sand, portland pozolan cement and styrofoam at 200, 350 and 15 kilograms, respectively with water cement ratio is 0.45 for 1 m3 and each specimens were reinforced by string of plastic with 10 mm diameter and distance 84 mm ; 14 mm diameter with distance 165 mm. The testing material is tested its flexural strength with four–point loading at 450 mm from each bearings.Value of tension stress of string plastic 10 mm diameter = 51.938 MPa and 14 mm diameter = 48.331 MPa, bond strength between the reinforcement and the concrete is 0.491 MPa for string plastic 10 mm diameter and 14 mm diameter is 0.341 MPa, value of modulus of rupture is 0.459 MPa. The result from the flexural test show that maximum loading for plate without string of plastic were 450 N; with string of plastic 10 mm diameter = 470 N and 14 mm diameter is 545 N and value maximum deflection of plate without string of plastic = 0.495 mm; with string of plastic 10 mm diameter = 4.745 mm and 14 mm diameter = 1.655 mm. Based on allowable maximum deflection specified by SK SNI, which is Dmax = 7.5 mm (L/180). Heavy of roof plate with reinforcement from string of plastic light progressively with existence reinforcement.